The Power of Humanitarian Narratives: A Domestic Coalition Theory of Justifications for Military Action. (September 2020) - Maxey, Sarah
Conventional wisdom assumes the best way to mobilize public support for military action is through the lens of national security. Humanitarian justifications provide a helpful substitute when US interests are not at stake, but are less reliable. However, US presidents have provided humanitarian explanations for every military intervention of the post-Cold War period. What, if any, power do humanitarian justifications have in security-driven interventions? The article answers this question by developing a domestic coalition framework that evaluates justifications in terms of whose support matters most in the build-up to intervention. Survey experiments demonstrate that humanitarian narratives are necessary to build the largest possible coalition of support. However, presidents risk backlash if they stretch humanitarian claims too far. Data from thirteen waves of Chicago Council surveys and an original dataset of justifications for US interventions confirm that humanitarian justifications are a common and politically relevant tool. The findings challenge both the folk realist expectation that the public responds primarily to threats to its own security and the constructivist tendency to limit the power of humanitarian justifications to cases of humanitarian intervention. Instead, humanitarian justifications are equally, if not more, important than security explanations for mobilizing domestic support, even in security-driven interventions.